Analisis Peran Tokoh Adat dalam Promosi Kesehatan Masyarakat di Daerah Terpencil - Marwono, Marwono; Pannyiwi, Rahmat; Harlina, Harlina; Pramono, Edi; Susanti, Susi (Barongko: Jurnal Ilmu Kesehatan, 2025)
Traditional leaders play a crucial role in the social structure of remote communities, particularly in influencing social behavior and norms, including health behaviors. This study aims to analyze the role of traditional leaders in community health promotion in remote areas. The method used was a descriptive qualitative approach using in-depth interviews with traditional leaders, health workers, and the community in District X. The results indicate that traditional leaders act as facilitators, messengers, and guardians of cultural values, increasing community awareness and acceptance of health programs. The active involvement of traditional leaders has been shown to increase the effectiveness of health promotion, particularly in immunization programs, environmental sanitation, and maternal and child care. It is concluded that integrating the role of traditional leaders into health promotion strategies can be an effective approach to improving community health status in remote areas.